(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: To investigate the role of allergy in nasal polyposis. Methods: 60 patients of nasal polyposis were selected randomly in a multicentric prospective trial from July 2006 to July 2008. Data were collected from the patient by personal interview, clinical examination and laboratory tests in a prescribed protocol. Socio-demographic character and presentation of the samples were studied and according to the symptoms of allergy those were submitted to skin pick test with a large series of seasonal and perennial airborne allergens. Results were presented in a tabulated form. Results: The incidence of nasal polyposis was highest among the people of 5th decade (40%) with male predominance (53.33%). The majority of the patients came from rural area (76.67%) and most of them were farmer (50%) and came from relatively poor class (73.33%). All the patients presented with significant nasal obstruction (100%). Next common presentations were running nose 90%, headache 80%, sneezing 70% and nasal itching 40%. Severity of symptoms increased with the exposure of national allergens (20%), food allergens (30%) and drugs (3.33%). 10% of patients were suffering from bronchial asthma. 20% patients with nasal polyposis were positive on Skin prick tests(SPT) with airborne allergens. A review of the clinical histories of SPT-positive patients revealed the presence of obstructive rhinitis and chronic rhinorrhea in most cases, whereas acute symptoms, such as sneezing and itching, were reported by a minority of subjects. Conclusion: Clinically evident respiratory allergies, particularly to perennial airborne allergens, play a relevant role in the pathogenesis of nasal polyposis. Key words: Allergic rhinitis; nasal polyposis. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8851 BJO 2011; 17(2): 117-120